Oratoria e umorismo latino in Cicerone: idee per l’inventio tra ars e tradizione - Oratory and Latin Humour in Cicero: Inventio between Ars and Tradition - Francesca Boldrer (Ciceroniana On Line, 2020)
This paper studies the significance of humour in Roman oratory, a theme dear to Cicero, who claimed expertise in it, and central to book 2 of the De oratore. In a long passage of the work (§§ 216-290), Cicero offers a detailed and systematic account of inventio that fleshes out the sketch presented in the Rhetorica ad Herennium. I argue that Cicero treats this controversial topic in Roman oratory with a sensitivity to the broad range of differing viewpoints held by established orators (including his own teachers). He does so by expertly managing the fine distinction between innovation and tradition, between Greek theoretical works and anthologies of Latin jokes (some of which were compiled by members of illustrious gentes), between utilitas and humanitas.